Proteomic Analysis of Microbial Community Inhabiting Asian Dust Source Region. Issue 1 (13th November 2015) - Sekhon, Simranjeet Singh; Kim, Mina; Um, Hyun‐Ju; Kobayashi, Fumihisa; Iwasaka, Yasunobu; Shi, Guangyu; Chen, Bin; Cho, Sung‐Jin; Min, Jiho; Kim, Yang‐Hoon
Abstract : The Asian desert dust storm originating from desert regions of northern China negatively influences plant and human health causing various diseases. The soil samples collected from the dust storm site were characterized by a meta‐proteomic approach using an automated two‐dimensional liquid phase fractionation system and matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry. Thirty‐eight proteins were detected and identified using Expasy database as a frame of reference. The samples consisted of various bacterial species including plant pathogens and soil bacteria which cause diseases. Soil proteomics provides a deeper analysis and better understanding of the microbial community. Abstract : Samples of Asian dust originating from the desert regions of northern China transporting microbial fractions were characterized by a meta‐proteomic approach. Thirty‐eight proteins from a total of 104 proteins are identified using Expasy database. Asian dust consists of various bacterial species, plant pathogens, and soil bacteria which cause diseases. Soil proteomics provides a deeper understanding of its microbial community.